SELECTION OF THE COMBINED UNIT'S WORKING BODY FOR THE INLINE SOIL SOFTENER - Nurabaev B. U.; Nurabaev J. J.; Mirzabaev T. S. (Journals Park Publishing, 2022)
In the article, all technological methods of leading and pre-sowing cultivation of land without land turnover and consecutively are taken into consideration in order to prevent compaction of the earth and destruction of the system, excessive compaction and destruction of the system, to reduce labor costs, energy costs, and fuel costs. The note describes the process and how it moves across the field one step at a time; machines and aggregates that create the processes are developed and widely used.
Keywords: combined unit, flat-cutting knives, spiral trowel, rotary softener, subtropical desert border, soil physical and mechanical properties